Quantitation of micro and nanoplastics in human blood by pyrolysis-gas chromatography–mass spectrometry - Marthinus Brits; Martin J. M. van Velzen; Feride Öykü Sefiloglu; Lorenzo Scibetta; Quinn Groenewoud; Juan J. Garcia-Vallejo; A. Dick Vethaak; Sicco H. Brandsma; Marja H. Lamoree (Microplastics and Nanoplastics)
Abstract The limited available data on human internal exposure poses a significant challenge in assessing the risks associated with micro and nanoplastics (MNPs) to human health. A contributing factor to this challenge is the scarcity of sensitive analytical methods to quantify the mass concentration of plastic polymers in human blood. In this study we present an improved and validated method for quantitatively analysing polyethylene (PE), polyethylene terephthalate (PET), poly(vinyl chloride) (PVC), poly(methyl methacrylate) (PMMA), polypropylene, and polystyrene in human whole blood samples. We introduce and apply stringent quality assurance and quality control procedures, including the validation of the method using quality control samples and continuous monitoring of batch analyses to ensure data reliability. Expanding upon prior pioneering work by Leslie et al. (2022), we optimised the pyrolysis-gas chromatography–mass spectrometry (Py-GC-MS) conditions to enhance method sensitivity and selectivity. Recovery experiments demonstrated a high level of accuracy and precision, with values ranging from 68 to 109% for quality control samples. Applying this method to whole blood samples (n = 68), we identified plastic polymers in 64 samples, with PE as the predominant polymer, followed by PVC, PET, and PMMA. In 17 blood samples, polymer concentrations were found to exceed the limit of quantitation, with a mean of 1070 ng/mL for the summed polymer concentrations, ranging between 170 and 2490 ng/mL. The mean of the sum of polymers across all blood samples (n = 68) was 268 ng/mL. These findings underscore the pressing need for further research aimed at comprehensive MNP quantification in human matrices, considering the potential health implications.